Comparative evaluation of punica granatum and pergularia daemia linn for its anthelmintic potential - RAMAN R CHANDAK; SACHIN N WAGH; SUBHASH J DEVDHE (International Journal of Pharma and Bio Sciences, 2011)
Methanolic extracts from the leaves of Pergularia daemia Linn. and leaves of Punica granatum are investigated for their anthelmintic activity against the earthworm Pheretima posthuma. Three concentration (50,100 and 150 mg/ml) of each extracts studies for anthelmintic activity, which involves the determination of time of paralysis and time of death of the worm. Both the extracts exhibit significant anthelmintic activity at highest concentration of 150 mg/ml. Albendazole in concentration of 25 mg/ml has been used as standard reference. Determination of paralysis time and death time of the worms were recorded. Dose dependent activity was observed in both plant extracts but Pergularia daemia Linn shows more activity as compared to Punica granatum.